A novel ultrasound-responsive cluster bomb system for efficient siRNA delivery in brain - Tianyu Guo; Feihong Dong; Jingyi Yin; Xinnan Wang; Pengting Min; Jiabin Zhang; Heping Cheng; Jue Zhang (Ultrasonics Sonochemistry, 2025)
RNA-based therapeutics using RNA interference have become a research hotspot for brain tumors and neurodegenerative diseases with the advancement of nanocarrier delivery technology. However, even with specific modifications, RNA-loaded nanoparticles face significant challenges in effectively crossing the blood-brain barrier (BBB) to achieve precise delivery of therapeutic agents to the brain. Focused ultrasound combined with microbubbles and nanodroplets has emerged as a promising approach for temporarily opening the BBB. However, the low drug loading capacity and fixed stimulation focus of these methods limit their integration with current nano-drug delivery systems. Herein, we introduced a fluorinated surfactant and developed an ultrasound-responsive siRNA delivery carrier that contains nanodroplets loaded with siRNA-carrying nanoparticles (siRNA@NP@ND), termed as “ultrasound-responsive ’cluster bomb’ nanoplatform”. Under precise and flexible guidance and stimulation through a programmable diagnostic ultrasound, siRNA@NP@ND demonstrated over a seventy-fold increase in efficiency for delivering siRNA to the mouse brain. Additionally, Evans blue staining and hematological analysis indicated that ultrasound-triggered cavitation could reversibly open the BBB for up to 48 h without causing significant immune or inflammatory responses. The minor intracranial hemorrhage resulting from this process was also shown to be recoverable. Our research provides an advanced and controllable delivery platform for gene therapy of intracranial central nervous system diseases.